Ethnomedicinal Plants of Sunderdhunga Valley, Western Himalaya, India - Traditional Use, Current Status and Future Scenario - Rawat, Balwant; Chandra Sekar, K.; Gairola, Sanjay (Indian Forester, 2013)
The Sunderdhunga valley harbors a number of medicinal plants used by the local people in different purposes. A total of 76 ethnomedicinal plants have been enumerated in the present communication with correct binomials, family, life form, local name along with detailed ethnomedicinal uses. These species belong to 27 families and 56 genera. Out of total species recorded, 82% belongs to only 11 families, on the other hand 48% of total families represented by single species. Fifteen of the recorded species are categorized under different threat category, constituting about 20% of total species. Major cause of depletion of these species is over exploitation of the wild populations and illegal trade. Important measures required to conserve the biodiversity of the valley include documentation of the traditional ecological and remedial knowledge of the locals for sustaining future generation and motivation to cultivate rare or threatened species in nearby villages.